Prevention of Child Marriage by the KUA of Kraksaan District through Partnership: A Perspective of Lawrence Meir Friedman's Legal System Theory - Anwari, Ahmad Hirzan; Mahmudi, Zaenul; Toriquddin, Moh (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to discuss the prevention of child marriage by the Religious Affairs Office (KUA) of Kraksaan District through partnerships in the review of Lawrence Meir Friedman's legal system theory. This is due to the high number of child marriage applications recorded at the KUA of Kraksaan District from 2022 to 2023. Then, the effectiveness of preventing child marriage will be measured through Lawrence Meir Friedman's legal system theory. Qualitative methods are used in this research. Qualitative methods are research methods based on philosophy and are useful for studying scientific conditions (experiments). In this partnership strategy, the KUA works with several partners, including Village Officials, Village Heads, Non-Civil Servant Employees/Counselors, Community Health Centers (PUSKESMAS), Kraksaan District Government, NU, Muhammadiyah and al-Irsyad. As a result, 50 applications were prevented, and five were postponed out of 55 applications in 2022. In 2023, 13 applications were successfully rejected, and nine were accepted out of 22 applications in 2023. In the review of Lawrence Meir Friedman's legal system theory, the substance of the law is Law No.16 of 2019. This law is not effective because Article 7 still provides an opportunity for people to marry children. Meanwhile, the legal structure comprises the structural officials of the KUA. The KUA, assisted by its partners, is said to be effective in preventing child marriage, as seen from the data on the success rate of preventing child marriage mentioned above. The legal culture is the people of Kraksaan Subdistrict who still strongly hold the tradition of arranged marriage, maintain the good name of the family, parents want to escape their responsibilities, and the belief that many families will provide a lot of sustenance.